The Forfeiture of the Convict's Assets Obtained from the Corruption Crime - Yoga Ristamana; Umar Ma'ruf; R. Sugiharto Sugiharto (Universitas Islam Sultan Agung, 2022)
The practice of corruption in Indonesia occurs in almost every layer of the bureaucracy, both legislative, executive and judicial, and has even become entrenched and has also spread to the business world, making it very difficult to change it. That uncovering criminal acts of corruption, finding the perpetrators and placing the perpetrators of criminal acts in prison has not been effective in reducing the level of corruption crimes, especially if it is not accompanied by efforts to confiscate and confiscate the proceeds of corruption. This study was conducted to determine the implementation of the seizure of assets convicts of corruption in the criminal act of corruption Jiwasraya. This study uses an empirical juridical approach with descriptive analytical research specifications, types and sources of data, namely primary data by conducting interviews and secondary data by conducting library research. The results of the study indicate to determine the implementation of the seizure of assets convicts of corruption in the criminal act of corruption Jiwasraya. The inhibiting factor is that many goods resulting from corruption have been transferred to other parties as well as legal constraints, while efforts to overcome them are that clear rules are needed to carry out the seizure of assets belonging to the Jiwasraya corruption convicts, and cooperation with related parties is needed to facilitate the implementation of asset confiscation convicted of corruption.